Biological and immunological characteristics of the poison of Bothrops cotiara (Serpentes: Viperidae) - de Roodt, Adolfo Rafael; Estévez, Judith; Dolab, Jorge Adrián; Manzanelli, Marcelo Víctor; Piñeiro, Nicolás; Paniagua, Jorge Francisco; Urs Vogt, Alejandro (Revista de Biología Tropical, 2006)
Bothrops cotiara is a venomous snake sporadically found in the province of Misiones in Argentina, South of Brazil and Paraguay. Data on the clinics of the envenomation produced by its bite and on its venom are scarce. There is no information on the neutralizing capacity of the antivenoms available. In this study, the lethal potency, hemorrhagic, necrotizing, coagulant and thrombin-like, defibrinogenating, indirect hemolytic and fibrinolytic activities of the venom of B. cotiara specimens from the province of Misiones were determined. The toxic activities were within the range of those described for the other Bothrops species from Argentina, and the electrophoretic and chromatographic studies showed similarities with those described for the other bothropic venoms. The immunochemical reactivity of six South American anti Viper antivenoms (ELISA) have a strong reactivity with all the antivenoms studied. The neutralizing capacity of three of these therapeutic antivenoms against the lethal potency and hemorrhagic, necrotizing, coagulant, thrombin-like and hemolytic activities showed a very close neutralizing capacity. Our data strongly suggest that the antivenoms for therapeutic use available in this area of South America are useful to neutralize the toxic and enzymatic activities of the venom of this uncommon specie of Bothrops.